Las redes del conflicto: el caso del Valle del Cauca - Castillo, María del Pilar (Sociedad y Economía, 2004)
This paper applies graph theory’s tools to the analysis of the armed conflict in the Valle del Cauca region. Armed agents are studied like networks which interact with each other in local contexts, but have global effects. Geographical places are represented by nodes of a graph, and to each node is associated a state of control that emerges from the original interaction setting. Results include localization preferences, non correlation between activity on adjacent nodes, and concentration of actions on individual nodes. All results depend on agents’ local interaction.